Post-traumatic stress disorder in the Ethiopian population dwelling in war-affected communities: a systematic review and meta-analysis - Tinsae, Techilo; Shumet, Shegaye; Tadesse, Gebresilassie; Takelle, Girmaw Medfu; Rtbey, Gidey; Melkam, Mamaru; Andualem, Fantahun; Nakie, Girum; Segon, Tesfaye; Koye, Selam; Fentahun, Setegn; Alemu, Wondale Getinet (Frontiers in Psychiatry, 2024)
Background: Post-traumatic stress disorder (PTSD) is a significant mental health concern globally, particularly prevalent in populations exposed to war and conflict. This systematic review and meta-analysis aim to examine the prevalence and factors associated with PTSD among the Ethiopian population residing in war-affected communities.The review was reported according to the PRISMA guidelines. Related eligible published articles were searched in electronic online databases such as PubMed, Scopus, Web of Science, MEDLINE/PubMed, Scopus, Embase, Science Direct, Web of Science, Google Scholar, and Google, which reported the prevalence and risk factors of PTSD among people dwelling in the war-affected area until January 2024. The relevant data was extracted using a Microsoft Excel spreadsheet. The meta-analysis was conducted using STATA version 11. The estimated pooled prevalence and risk factors were estimated using a random effect model. The potential risk of publication bias was checked using a funnel plot and Egger's statistical test.Results: A total of nine published studies with 6107 participants were analyzed in this metaanalysis. The estimated pooled prevalence of PTSD among people living in war-affected areas was 48.4%, with a 95% CI (37.1, 59.8). This study found a higher prevalence of PTSD among women than men. Being female (OR= 2.2, 95% CI: 1.2, 4.3), witnessing a murder of a loved one (OR= 3.0, 95% CI: 1.2, 7.5), depression symptoms (OR= 2.8, 95% CI: 1.4, 5.6), and anxiety symptoms (OR= 3.4, 95% CI: 1.4, 8.0), a close family member killed or seriously injured (OR= 3.1, 95% CI: 1.2, 7.7), a moderate and high perceived threat to life (OR= 3.4, 95% CI: 1.3, 9.1), and poor social support (OR= 4.4, 95% CI: 1.1, 18.7) were associated with post-traumatic stress disorder.The result of this study shows the high prevalence rate of PTSD in people living in war-affected areas. disparities in PTSD prevalence, with women being at higher risk, and identified risk factors were witnessing the murder of a loved one, experiencing depression and anxiety, and perceived threat to life. Addressing PTSD in war-affected communities requires comprehensive interventions that consider both individual and contextual factors.